2016
DOI: 10.1186/s12967-016-0811-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated transfer of miR-222 is sufficient to increase tumor malignancy in melanoma

Abstract: BackgroundGrowing evidence is showing that metastatic cell populations are able to transfer their characteristics to less malignant cells. Exosomes (EXOs) are membrane vesicles of endocytic origin able to convey their cargo of mRNAs, microRNAs (miRs), proteins and lipids from donors to proximal as well as distant acceptor cells. Our previous results indicated that miR-221&222 are key factors for melanoma development and dissemination. The aim of this study was to verify whether the tumorigenic properties assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 52 publications
5
131
0
Order By: Relevance
“…Similarly, expression of miR-31 was reported to be down-regulated in polycystic kidney disease (Pandey et al 2008), whereas in exosomes from CKD patients we found it to be significantly increased. Also, miR-222 has been demonstrated to be upregulated in exosomes from melanoma cells, promoting Identification of urinary exosomal noncoding RNAs www.rnajournal.org 145 tumorigenesis by activating the PI3K/AKT pathway (Felicetti et al 2016). MiR-877 is significantly down-regulated in blood and renal cell carcinoma (RCC) tissues and is considered a potential biomarker for RCC diagnosis (Shi et al 2016).…”
Section: Differential Abundance Of Exosomal Mirnas In Ckd Patients Vementioning
confidence: 99%
“…Similarly, expression of miR-31 was reported to be down-regulated in polycystic kidney disease (Pandey et al 2008), whereas in exosomes from CKD patients we found it to be significantly increased. Also, miR-222 has been demonstrated to be upregulated in exosomes from melanoma cells, promoting Identification of urinary exosomal noncoding RNAs www.rnajournal.org 145 tumorigenesis by activating the PI3K/AKT pathway (Felicetti et al 2016). MiR-877 is significantly down-regulated in blood and renal cell carcinoma (RCC) tissues and is considered a potential biomarker for RCC diagnosis (Shi et al 2016).…”
Section: Differential Abundance Of Exosomal Mirnas In Ckd Patients Vementioning
confidence: 99%
“…miRNA, single-chain and non-coding RNA with a length of 18-25 nt, regulate gene expression at the post-transcriptional level (45). miRNA interact with mRNA and have been indicated to degrade target mRNA or inhibit target mRNA translation (7). A single miRNA may regulate several target mRNA, and multiple miRNA may also bind to one target mRNA (46).…”
Section: Biological Characteristics Of Exosomesmentioning
confidence: 99%
“…Previous studies have indicated that miRNA are also closely related to melanoma (7,(78)(79)(80). For instance, melanoma cells secrete exosomes carrying miR-222 to promote tumorigenesis by activating the phosphoinositide 3-kinase/AKT pathway (7).…”
Section: Exosomes and Skin Cancermentioning
confidence: 99%
See 2 more Smart Citations